Identification of Intestinal Parasites From Stool Specimens within One Year at Gaziantep University Medical Faculty Hospital - Ekşi, Fahriye; Doğan, Yusuf; Özdemir, Gül; Zer, Yasemin; Bayram, Ayşen; Karslıgil, Tekin (Fırat University, 2013)
Objective: In this study, data from 5,453 stool samples collected from patients presented with a variety of gastrointestinal symptoms between July 2011 and July 2012 was aimed to be evaluated retrospectively with parasitological aspects at the Microbiology Laboratory of Gaziantep University Medical Faculty. Material and Method: Examination of stool samples was performed with native-lugol method and trichrome or acid-fast stained samples were prepared in suspected cases. Results: From a total of 5,453 stool samples, one or more parasites were found in 813 samples (14.91%) and 4,640 samples (85.09%) were free from parasites. Entamoeba histolytica/dispar trophozoites/cysts were detected in 679 (12.45%), Giardia intestinalis in 117 (2.15%), Hymenelopis nana in 7 (0.13%), Taenia spp. in 6 (0.11%), Enterobius vermicularis in 2 (0.04%), and Isospora belli, Strongyloides stercoralis and Trichuris trichura in 1 sample each (0.01%). As gender and age groups were analyzed, parasites were detected in 460 (15.10%) of samples obtained from male patients, in 353 (14.67%) obtained from female patients, in 315 (11.4%) of the pediatric age, and in 498 (19.15%) of the adult age group. In our study, the detec-tion rates of parasites according to months were analyzed; April (18.66%), August (18.53%), July (17.92%) and September (17.68%) were the most commonly parasite detected months. Conclusion: This study highlights the feature of intestinal parasitic infections being a serious public health problem in our city.

Amaç: Bu çalışmada, Temmuz 2011- Temmuz 2012 tarihleri arasında Gaziantep Üniversitesi Tıp Fakültesi Mikrobiyoloji Laboratuvarına, çeşitli gastrointestinal yakınmalarla başvuran hastalardan toplanan 5453 gaita örneğine ait verilerin retrospektif olarak parazitolojik açıdan değerlendirilmesi amaçlanmıştır. Gereç ve Yöntem: Gaita örnekleri nativ-lugol inceleme ve şüpheli olgularda trikrom ve asit fast boyalı preparasyonlar hazırlanarak araştırılmıştır. Bulgular: Örneklerin 813'ünde (% 14.91) bir veya birden fazla parazit saptanmış, 4640 (%85,09) örnekte parazite rastlanmamıştır. Örnekler içerisinde 679'unda (%12.45) Entamoeba histolytica/dispar trofozoit/kisti, 117'sinde (%2.15) Giardia intestinalis, 7'sinde (%0.13) Hymenelopis nana, 6'sında (%0.11) Taenia spp., 2'sinde (%0.04) Enterobius vermicularis, 1'inde (%0.01) İsospora belli, 1'nde (%0,01) Strongyloides stercoralis, 1'nde (%0,01) Trichuris trichura saptanmıştır. Cinsiyet ve yaş grupları incelendiğinde, erkek hastalardan elde edilen örneklerin 460'ında (%15.10), kadın hastalardan elde edilen örneklerin 353'ünde (%14.67), çocukluk yaş grubundaki hastaların 315'inde (%11.04), erişkin yaş grubundakilerin 498'inde (%19.15) parazit saptanmıştır. Çalışmamızda, incelenen örnekler içerisinde aylara göre parazit saptanma oranlarına bakıldığında, Nisan (%18.66), Ağustos (%18.53), Temmuz (%17.92) ve Eylül (%17.68) ayları en sık parazit saptanan aylar olarak belirlenmiştir. Sonuç: Bu çalışma, bağırsak parazit enfeksiyon'larının ilimizde ciddi bir halk sağlığı sorunu olma özelliğini vurgulamaktadır.
Gaziantep Üniversitesi Tıp Fakültesi Hastanesi'nde Bir Yıllık Sürede Gaita Örneklerinde Saptanan Bağırsak Parazitlerinin Dağılımı